PENDUGAAN ALIRAN DASAR (BASEFLOW) DI DAERAH TANGKAPAN AIR WADUK GAJAH MUNGKUR DI HULU DAS BENGAWAN SOLO, JAWA TENGAH. (Estimating baseflow for a catchment area of Gajah Mungkur Reservoir in the upstream of Bengawan Solo watershed, Central Java) - Prasetyo Nugroho; Hatma Suryatmojo; Giska Parwa Manikasari; Hafsa Nur Afisena (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2021)
ABSTRACT The upstream area of watersheds has a strategic role in controlling the water cycle, including controlling direct runoff to increase base flow and guide the fluctuation of river discharge. The objective of this study is to determine the base flow of Gajah Mungkur catchment area, which is located in the upper stream of the Bengawan Solo watershed, after 18 years of rehabilitation. To understand the base flow, river discharge measurements for 4 months were carried out at the River Discharge Observation Station (SPAS) which are equipped with automatic rainfall and water level recorders. Data analysis includes vegetation analysis, river discharge analysis, hydrograph analysis, and baseflow index (BFI) analysis. The total rain during the study was 45.8 mm and the average air temperture was 22.45˚ C. The pine forest density varied from low to high, with tree densities ranging from 569 - 919 trees/hectare. Results show that the BFI value in April-August 2017 is 44.63%. The increase of trees age in the Gajah Mungkur catchment area followed by changes in stand structure is considered to increase the ability of buffering capacity and regulating the area's water cycle.Keywords: base flow, pine forest, upstream, forest rehabilitation. ABSTRAKKawasan hulu Daerah Aliran Sungai (DAS) memiliki peran strategis dalam pengendalian daur air, diantaranya adalah perannya dalam mengendalikan aliran permukaan untuk meningkatkan aliran dasar (baseflow) dan menjaga fluktuasi aliran sungai. Penelitian ini bertujuan untuk mengetahui besarnya aliran dasar setelah 18 tahun direhabilitasi dengan studi kasus di DTA Gajah Mungkur yang terletak di hulu DAS Bengawan Solo. Pengukuran debit aliran selama 4 bulan dilakukan di Stasiun Pengamatan Aliran Sungai (SPAS) yang dilengkapi dengan alat perekam hujan dan debit aliran otomatis. Analisis data yang dilakukan meliputi analisis vegetasi, analisis debit aliran sungai, analisis hidrograf aliran dan analisis Baseflow Index. Total hujan selama penelitian yaitu 45,8 mm dengan suhu udara rata-rata 22,45˚C. Kondisi kerapatan tegakan bervariasi dari kerapatan rendah sampai dengan tinggi, dengan kerapatan pohon berkisar antara 569 -  919 pohon/ ha. Hasil analisis menunjukkan bahwa nilai BFI pada bulan April-Agustus 2017 yaitu 44,63%. Pertambahan umur tegakan di DTA Gajah Mungkur sampai pada umur 18 tahun diikuti dengan perubahan struktur tegakan sehingga diduga berdampak pada meningkatnya kemampuan penyangga dan pengaturan daur air kawasan. Kata kunci: aliran dasar; hutan pinus; hulu daerah aliran sungai; rehabilitasi hutan